2003
DOI: 10.1152/jn.00716.2002
|View full text |Cite
|
Sign up to set email alerts
|

Neural Pathways Between Sacrocaudal Afferents and Lumbar Pattern Generators in Neonatal Rats

Abstract: Strauss, I. and A. Lev-Tov. Neural pathways between sacrocaudal afferents and lumbar pattern generators in neonatal rats. J Neurophysiol 89: 773-784, 2003; 10.1152/jn.00716.2002. Projections of sacrocaudal afferents (SCA) onto lumbar pattern generators were studied in isolated spinal cords of neonatal rats. A locomotor-like pattern could be produced by SCA stimulation in the majority of the preparations. The SCA-induced lumbar rhythm was abolished after blocking synaptic transmission in the sacrococcygeal (SC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 44 publications
3
67
0
Order By: Relevance
“…Recent clinical studies have shown that reactivation of the CPGs in spinal cord injury patients by afferent input is possible, and that it improves the motor function and mobility of patients with incomplete thoracic spinal injury (Wernig et al, 1995;Colombo et al, 2001;Dietz et al, 2002;Dietz and Harkema, 2004;Dietz, 2009). Our findings that stimulation of sacrocaudal afferents (SCAs) in the isolated spinal cord of the neonatal rat is a potent activator of the pattern generating circuitry in the sacral and limb moving segments Delvolvé et al, 2001;Strauss and Lev-Tov, 2003;Gabbay and Lev-Tov, 2004;Blivis et al, 2007; also see Whelan et al, 2000, for the neonatal mouse) enable us to use this preparation to study the functional organization and mechanism of action of the pathways that are involved in sensory-activation of the CPGs, under controlled in vitro conditions. Our previous work revealed that the SCA-induced rhythm is not generated by direct contacts between the stimulated afferents and the hindlimb CPGs, but that it involves synaptic activation of sacral neurons whose axons project to the hindlimb innervating segments of the spinal cord through the white matter funiculi (Strauss and Lev-Tov, 2003;Lev-Tov and O'Donovan, 2009;Lev-Tov et al, 2010).…”
Section: Introductionmentioning
confidence: 67%
“…Recent clinical studies have shown that reactivation of the CPGs in spinal cord injury patients by afferent input is possible, and that it improves the motor function and mobility of patients with incomplete thoracic spinal injury (Wernig et al, 1995;Colombo et al, 2001;Dietz et al, 2002;Dietz and Harkema, 2004;Dietz, 2009). Our findings that stimulation of sacrocaudal afferents (SCAs) in the isolated spinal cord of the neonatal rat is a potent activator of the pattern generating circuitry in the sacral and limb moving segments Delvolvé et al, 2001;Strauss and Lev-Tov, 2003;Gabbay and Lev-Tov, 2004;Blivis et al, 2007; also see Whelan et al, 2000, for the neonatal mouse) enable us to use this preparation to study the functional organization and mechanism of action of the pathways that are involved in sensory-activation of the CPGs, under controlled in vitro conditions. Our previous work revealed that the SCA-induced rhythm is not generated by direct contacts between the stimulated afferents and the hindlimb CPGs, but that it involves synaptic activation of sacral neurons whose axons project to the hindlimb innervating segments of the spinal cord through the white matter funiculi (Strauss and Lev-Tov, 2003;Lev-Tov and O'Donovan, 2009;Lev-Tov et al, 2010).…”
Section: Introductionmentioning
confidence: 67%
“…Therefore, the relatively high level of recovery reported by Leblond et al 15 was most likely attributable to afferent-induced activation of the central pattern generator (CPG), caused by tail stimulation. 21 We cannot exclude the possibility that, in both studies, some of the recovery was facilitated or partially caused by repeated testing sessions over time which could constitute some form of training-induced effects upon CPG reorganization and activation.…”
Section: Discussionmentioning
confidence: 90%
“…We did not consider LMs or NLMs induced during bowel movements to avoid nonrelated afferent (sacral) stimulation-induced movements. 12 Amplitude was characterized by assigning one of the three values; 0Fno movement; 1Fmovements considered to be less than half the range of motion of a normal step; 2Fmovements considered to be greater than half the range of motion of a normal step.…”
mentioning
confidence: 99%